Sex-based immunological differences in multisystem inflammatory syndrome in children: potential role of TR3–56 cells for pathogenesis, diagnosis, and therapy - Carriero, Flavia; Gelzo, Monica; Rubino, Valentina; Scalia, Giulia; Castaldo, Alice; Tipo, Vincenzo; Giannattasio, Antonietta; D’Anna, Carolina; Ruggiero, Giuseppina; Castaldo, Giuseppe; Terrazzano, Giuseppe (Frontiers in Immunology, 2025)
Multisystem Inflammatory Syndrome in Children (MIS-C) is characterized by immune dysregulation, exhibiting clinical and immunological features reminiscent of autoimmune processes, although its underlying mechanisms remain incompletely understood. This study examines immune system alterations in MIS-C patients, focusing on TR3–56 lymphocytes, a novel population of regulatory T cells. Our findings reveal a positive correlation between circulating TR3–56 cells and regulatory T cells, suggesting a potential immunoregulatory role in MIS-C pathogenesis. Furthermore, we identified significant sex-based differences in immune responses. Male patients exhibit higher percentages of TR3–56 lymphocytes and increased expression of T cell activation markers, which correlate with greater disease severity. Conversely, female patients display immune profiles characterized by stronger immune T cell memory and regulatory responses, potentially helping to modulate inflammation. These findings highlight the relevance of considering sex-based differences in immune responses to MIS-C and suggest that TR3–56 lymphocytes may serve as novel biomarkers and potentially as therapeutic targets. Our study enhances the understanding of immune dysregulation in MIS-C and underscores the need for sex-specific therapeutic strategies to improve patient outcomes.